Analysis of Slang Language Found in The Song Lyrics “Enema of The State” Album By BLINK-182 - Laksono, Riva Guntur; Meiga Ratih Tirtanawat; Chyntia Heru Woro Prastiwi (Jurnal Cakrawala Akademika, 2024)
This research includes a slang analysis of the lyrics of selected songs from Blink-182's "Enema of The State" album. The purpose of this study is to classify the types of slang that appear in the lyrics of Blink-182's album ``enema of the state'' and clarify the meaning of the slang. In this research, the author uses descriptive and qualitative methods. The data source for this research is a selection of Blink-182 song lyrics from the album "Enema of The State." Five types of slang are used in this song: Colloquial slang, pejorative slang, expressive slang, self-deprecatory slang, and vulgar slang. Colloquial slang is the type of slang that appears most often in selected blink-182 songs.